Distribution of laminin, fibronectin, and interstitial collagen type III in soft tissue tumours. Issue 8 (August 1984) - d'Ardenne, A J; Kirkpatrick, P; Sykes, B C
Abstract : The distributions of laminin, fibronectin, and interstitial collagen type III have been investigated in a series of 60 soft tissue tumours by immunochemistry. Positive laminin staining was seen in sites predicted by the distribution of ultrastructurally visible basal lamina. Pericellular laminin was present in all benign tumours of Schwann cell and smooth muscle origin examined, in the two malignant Schwannomas examined, and in six of 13 leiomyosarcomas. It was also evident around nests of cells in an alveolar soft part sarcoma and around malignant endothelial cells in an angiosarcoma. In fibroblastic and fibrohistiocytic tumours it was found only in blood vessel walls. The results of laminin staining led to revision of the original histopathological diagnosis in seven of the 60 cases studied. Fibronectin was abundant in the stroma of most neoplasms, both benign and malignant. It was also found in a distribution parallel to that of laminin. In some tumours this was clearly distinguishable from the distribution of interstitial collagen. Intracellular fibronectin was shown consistently only in mast cell granules. Its demonstration in synovial cells, fibroblasts, and histiocytes was more variable. Interstitial collagen type II had the most irregular distribution of the three proteins. It was as plentiful in tumours of smooth muscle origin as in tumours of fibroblastic origin, but was scanty in fibrous histiocytomas. Its distribution appeared similar to that of laminin and fibronectin in leiomyomas, but differed from these two proteins in Schwann cell tumours and other neoplasms. In one leiomyosarcoma fibronectin, laminin, and type III collagen appeared to be lost concomitantly from tumour cell peripheries.